A Simultaneous Estimation of Clotrimazole and Its Impurities: Pharmaceutical Science-Pharmaceutical analysis for Novel drug formulation - P. Abhinandana; Ramarao Nadendla (International Journal of Life Science and Pharma Research, 2022)
A simple, efficient and reproducible method for the simultaneous determination of Clotrimazole and its Impurities (Imidazole and (2-chlorophenyl) phenyl methanone (2-chlorobenzophenone)) has been developed using reversed phase high performance liquid chromatography. The separation was carried out using a mobile phase consisting of Potassium dihydrogen phosphate buffer (pH 7.2): Acetonitrile (25:75 %v/v). Column used was SHIMADZU C18 (4.6x250 mm, 5 µm) with a flow rate of 0.8 ml/min and the column temperature was maintained at 40 °C. The detection wavelength used was at 220 nm. The retention time of Clotrimazole, Imidazole and 2-chlorophenyl phenyl methanone (2-chlorobenzophenone)was 8.12, 7.56 and 3.02 min respectively. Linearity of Clotrimazole and its Impurity are in range of 0.013-0.076 mg/mL. For System Suitability % RSD was found to be 1.60 for Clotrimazole, 1.29 for Imp-D, 1.15 for Imp-E..The Mean% Recoveries were found to be within the range of 98-102 %.Analytical parameters were calculated and a statistical evaluation was included.